The immobility turn mobility, migration and the Covid-19 pandemic - Cairns, David (Bristol University Press, 2023)
Using empirical evidence from Portugal, a geopolitically important point of intersection within Europe and between Global South and Global North, this book offers invaluable insights about how the pandemic has impacted migration, mobility, industries and individuals' lives, informing policy-making processes on a global level.